Dampak Penggunaan Teknologi Informasi dan Komunikasi terhadap Produk Domestik Regional Bruto (PDRB) Per Kapita Tingkat Provinsi di Indonesia - Haikal, Fikri; Anward, Ryan Juminta (PPJP ULM, 2023)
This research aims to determine the impact of increasing the use of information and communication technologies, in terms of cellular phones, computers, and the internet, on the provincial Gross Domestic Regional Product per capita in Indonesia. Static panel data regression using Within-Group Fixed Effect and dynamic panel data regression using System GMM is employed. The result shows that increasing the use of cellular phones, computers, dan the internet can promote provincial GDRP per capita. However, the impact caused by using ICTs is still relatively small.